PENGARUH EKSTRAK TEMULAWAK PADA PAKAN SEBAGAI IMUNOSTIMULAN PADA IKAN TAWES (Puntius javanicus) DENGAN UJI TANTANG BAKTERI - Astuti, Agustin Putri Kusuma; Hastuti, Sri; Haditomo, Alfabetian Harjuno Condro (Journal of Aquaculture Management and Technology, 2017)
Pakan adalah salah satu faktor penting yang mempengaruhi pertumbuhan. Peningkatan kinerja pertumbuhan dan pengendalian penyakit dapat dilakukan dengan penggunaan imunostimulan. Imunostimulan merupakan bahan yang mampu meningkatkan respon imun non spesifik ikan. Temulawak dapat memberikan imunostimulan yang mampu memberikan respon kekebalan tubuh ikan secara langsung terhadap antigen yang masuk ke dalam tubuh ikan. Salah satu kandungan temulawak adalah kurkumin yang dapat menghambat pertumbuhan dan mematikan mikroorganisme, salah satunya Aeromonas hydrophila. Penelitian ini bertujuan untuk mengkaji pengaruh ekstrak temulawak terhadap ketahanan tubuh ikan tawes yang diinfeksi A. hydrophila, kelulushidupan (SR), total konsumsi pakan (TKP), dan laju pertumbuhan relatif (RGR). Ikan uji yang digunakan adalah ikan tawes dengan bobot rata-rata 2,98±0,11 g/ekor. Pemberian pakan pada ikan uji sebanyak 2 kali sehari pada pukul 08.00 dan 16.00 secara at satiation. Ikan uji dipelihara dengan padat tebar 1 ekor/l dengan lama pemeliharaan 40 hari. Metode yang digunakan dalam penelitian ini adalah eksperimental menggunakan Rancangan Acak Lengkap dengan 4 perlakuan dan 3 kali ulangan. Perlakuan ini adalah pakan uji dengan penambahan ekstrak temulawak, dengan dosis sebagai berikut: perlakuan A (0 g/kg pakan); B (3 g/kg pakan); C (6 g/kg pakan) dan D (9 g/kg pakan). Hasil penelitian menunjukkan bahwa penambahan ekstrak temulawak memberikan pengaruh yang sama terhadap kondisi kesehatan ikan tawes, namun memberikan pengaruh yang berbeda (P<0.05) terhadap nilai SR, TKP dan RGR. Perlakuan dengan penambahan ekstrak dengan dosis 9 g/kg menunjukkan nilai tertinggi pada SR (82,00%) dan TKP (80,48 g). Kualitas air pada media pemeliharaan terdapat pada kisaran yang sesuai untuk budidaya ikan tawes (P. javanicus). Kesimpulan pada penelitian ini adalah bahwa penambahan ekstrak temulawak pada pakan dengan dosis 9 g/kg pakan memberikan hasil tertinggi pada SR dan TKP ikan tawes. Feed is one of the important factors that affect the growth. The increase in the performance growth and control of disease can be done by the use of imunostimulan. Immunostimulant is a material that capable of increasing the non-specific immune response of fish. Curcuma can provide immunostimulant that capable to providing immune response of fish directly to the antigen into the fish body. One of the content of curcuma is curcumin which can inhibit growth and kill microorganisms, one of them is Aeromonas hydrophila. This study aims to reviewing the effects of extracts curcuma of fish body resistance against infected by A. hydrophila, survival rate (SR), total feed consumption (TKP), and relative growth rate (RGR). The trial fish used in this study is java barb with the average body weight of 2.98 ± 0.11 g/fish. The test feed given twice times per day at 08.00and 16.00 by at satiation method. The fishes were cultured with stock density 1 fish/l with a 40 day maintenance period. The methodology used is experimental, using the randomized complete design with 4 treatments and 3 replicates. The treatments were A (0 g of curcuma/kg feed); B (3 g of curcuma/kg feed); C (6 g of curcuma/kg feed) and D (9 g of curcuma/kg). The results of research that the addition of curcuma extract in feed showed not significant on health conditions, but showed a significant (P<0.05) result toward SR, TKP, and RGR. Treatment by adding extract doses 9 g/kg shows on the highest the SR (82%) and TKP (80,48 g). Water quality in the maintenance media contained in a range that is suitable for the cultivation of java barb (P. javanicus). The conclusion of research is that addition to extract curcuma with a dose 9 g/kg results on the highest SR and TKP. Feed is one of the important factors that affect the growth. The increase in the performance growth and control of disease can be done by the use of imunostimulan. Immunostimulant is a material that capable of increasing the non-specific immune response of fish. Curcuma can provide immunostimulant that capable to providing immune response of fish directly to the antigen into the fish body. One of the content of curcuma is curcumin which can inhibit growth and kill microorganisms, one of them is Aeromonas hydrophila. This study aims to reviewing the effects of extracts curcuma of fish body resistance against infected by A. hydrophila, survival rate (SR), total feed consumption (TKP), and relative growth rate (RGR). The trial fish used in this study is java barb with the average body weight of 2.98 ± 0.11 g/fish. The test feed given twice times per day at 08.00and 16.00 by at satiation method. The fishes were cultured with stock density 1 fish/l with a 40 day maintenance period. The methodology used is experimental, using the randomized complete design with 4 treatments and 3 replicates. The treatments were A (0 g of curcuma/kg feed); B (3 g of curcuma/kg feed); C (6 g of curcuma/kg feed) and D (9 g of curcuma/kg). The results of research that the addition of curcuma extract in feed showed not significant on health conditions, but showed a significant (P<0.05) result toward SR, TKP, and RGR. Treatment by adding extract doses 9 g/kg shows on the highest the SR (82%) and TKP (80,48 g). Water quality in the maintenance media contained in a range that is suitable for the cultivation of java barb (P. javanicus). The conclusion of research is that addition to extract curcuma with a dose 9 g/kg results on the highest SR and TKP.